Antimicrobial Activities of Aztreonam-Avibactam and Comparator Agents against Contemporary (2016) Clinical Enterobacteriaceae Isolates - Sader, Helio S. (Antimicrob Agents Chemother, 2017)
A total of 10,451 contemporary (2016) Enterobacteriaceae isolates from 84 U.S. medical centers and 116 metallo-β-lactamase- and/or OXA-48-like-producing Enterobacteriaceae isolates from other countries were tested against aztreonam-avibactam and comparators. All U.S. isolates were inhibited at aztreonam-avibactam MICs of ≤8 μg/ml (MIC(50), ≤0.03 μg/ml; MIC(90), 0.12 μg/ml), including Klebsiella pneumoniae carbapenemase-producing isolates (n = 102; MIC(50), 0.25 μg/ml; MIC(90), 0.5 μg/ml), multidrug-resistant isolates (n = 876; MIC(50), 0.06 μg/ml; MIC(90), 0.25 μg/ml), and extensively drug-resistant isolates (n = 111; MIC(50), 0.12 μg/ml; MIC(90), 0.5 μg/ml). The highest aztreonam-avibactam MIC value among ex-U.S. isolates was 4 μg/ml.